2002
DOI: 10.1080/00015458.2002.11679303
|View full text |Cite
|
Sign up to set email alerts
|

Epidural cooling for regional spinal cord hypothermia during most or all of descending thoracic or thoracoabdominal aneurysm repair

Abstract: Perfusion cooling of the epidural space during most or all of the descending thoracic or thoracoabdominal aneurysm repair was effective in reducing postoperative spinal cord injury and a safe method in clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The main causes of spinal cord injury in two patients was instability of hemodynamics during the operation due to massive bleeding. Many authors have reported the importance of intercostal vessel reconstruction [3][4][5][6][7]11 It is as yet unclear whether critical intercostal arteries can be identifi ed during operation. Isolated intercostal or lumbar arteries are reimplanted if they are large or if there is little or no back-bleeding; vigorous backbleeding from small intercostal arteries is controlled by oversewing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main causes of spinal cord injury in two patients was instability of hemodynamics during the operation due to massive bleeding. Many authors have reported the importance of intercostal vessel reconstruction [3][4][5][6][7]11 It is as yet unclear whether critical intercostal arteries can be identifi ed during operation. Isolated intercostal or lumbar arteries are reimplanted if they are large or if there is little or no back-bleeding; vigorous backbleeding from small intercostal arteries is controlled by oversewing.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported the safety and protective effect of this method. [11][12][13] Postop, postoperative; CVA, cerebrovascular accident (A-shield). We usually reimplant the intercostal artery detected as the Adamkiewicz artery preoperatively and two or three pairs of intercostal arteries in the T8 to L1 region by interposition of a small graft.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, the mortality is 3.0%-23.0%, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and the incidence of spinal cord injury, the most devastating complication, is 3.0%-18.0%. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Those patients whose postoperative outcome is complicated by paraplegia or paraparesis not only suffer severe physical disability, but their long-term survival is known to be shorter. In the artery of Adamkiewicz by using multidetector-row helical computed tomography in 90% of patients.…”
Section: Introductionmentioning
confidence: 98%
“…The vascular surgery literature for thoracoabdominal aortic aneurysm repairs have shown that cooling the epidural space is potentially neuroprotective and safe. 53,77,78 The optimal temperature is not known. However, the use of normal saline chilled to 4°C to cool the epidural space to 25°C has been shown to be effective in minimizing postoperative neurological complications.…”
Section: Treatment Options After An Intraoperative Scimentioning
confidence: 99%